2010
DOI: 10.1016/j.ijpharm.2010.07.029
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different enhancers on the transdermal permeation of insulin analog

Abstract: Using chemical penetration enhancers (CPEs), transdermal drug delivery (TDD) offers an alternative route for insulin administration, wherein the CPEs reversibly reduce the barrier resistance of the skin. However, there is a lack of sufficient information concerning the effect of CPE chemical structure on insulin permeation. To address this limitation, we examined the effect of CPE functional groups on the permeation of insulin. A virtual design algorithm that incorporates quantitative structure-property relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 27 publications
(30 reference statements)
2
26
0
Order By: Relevance
“…Samples (1.0 ml) were withdrawn from the receiver compartment (5 ml) at different time intervals and replaced with 1.0 ml fresh PBS solution. Collected samples were stored at 25°C until further analysis [22,23]. DMSO (5 ml) was mixed into the collected sample solution for 1 h, followed by ultracentrifugation at 20 000 rpm for 30 min.…”
Section: Ex Vivo Tdds Permeation Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Samples (1.0 ml) were withdrawn from the receiver compartment (5 ml) at different time intervals and replaced with 1.0 ml fresh PBS solution. Collected samples were stored at 25°C until further analysis [22,23]. DMSO (5 ml) was mixed into the collected sample solution for 1 h, followed by ultracentrifugation at 20 000 rpm for 30 min.…”
Section: Ex Vivo Tdds Permeation Studiesmentioning
confidence: 99%
“…This motivates to optimize the formulation (size reduction) and the possibility of application in skin has been compared with available active methods. The role of CPE has been investigated over the years [22], and hence the highly permeable concentration of permeation enhancer (OA) was selected in this study for achieving high permeability of nanoemulsions. The skin penetration result showed that, when quercetin was incorporated in the nanoemulsions, the development of high permeable tiny nanoparticles was enhanced.…”
Section: Ex Vivo Permeation Studiesmentioning
confidence: 99%
“…Oleic acid acted as both a chemical permeation enhancer and as a surfactant to obtain a homogeneous nanoemulsion. 25,40 The nanoemulsion was diluted by adding water to make a final formulation of 70 mL. The acetone was removed, and the aqueous phase was concentrated by rotary evaporation at 40°C under reduced pressure.…”
Section: Preparation Of Plga Nanoparticles Containing Quercetin and Vmentioning
confidence: 99%
“…Utilization of chemical permeation enhancers in preparation of nanoparticles can overcome the barrier function of skin. [24][25][26] Different types of film dressing materials are available, including chitin, chitosan, Tegaderm™ (3M Health Care, Borken, Germany), hydrocolloid, biofilm, and alginate. 27,28 Alginate film is the most widely recommended dressing in the diabetic population, having a good safety profile and being suitable for application on wounds.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, transdermal topical delivery of conventional NSAIDs has been reported for ibuprofen and naproxen but not for sulindac (1720). Besides higher efficacy, topical delivery of compounds may be accompanied by enhanced safety, as, among others, lower doses are often needed to achieve therapeutic effects comparable to those from systemic drug application (21,22). This is an important consideration for diseases like RA that may require prolonged treatment with anti-inflammatory agents (3,4).…”
Section: Introductionmentioning
confidence: 99%